2020
DOI: 10.1093/cid/ciaa054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes and Low Body Mass Index on Tuberculosis Treatment Outcomes

Abstract: Background Diabetes was identified as a tuberculosis (TB) risk factor mostly in retrospective studies with limited assessments of metabolic variables. The prospective Effects of Diabetes on Tuberculosis Severity study compared adults with pulmonary TB in Chennai, India, who were classified as having either diabetes or a normal glucose tolerance at enrollment. Methods Baseline TB severity, sputum conversion, and treatment outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 36 publications
8
36
0
2
Order By: Relevance
“…In contrast to several retrospective reports and a systematic review in LMICs [ 8 , 11 , 27 ], our prospective analysis does not indicate an independent association between DM and composite unfavorable TB treatment outcome, consistent with a recent report from South India [ 28 ]. Traditional risk factors such as low BMI [ 29 , 30 ] and alcohol use [ 31 ] were associated with adverse outcomes; neither degree of hyperglygemia nor new DM was associated with unfavorable outcomes [ 28 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast to several retrospective reports and a systematic review in LMICs [ 8 , 11 , 27 ], our prospective analysis does not indicate an independent association between DM and composite unfavorable TB treatment outcome, consistent with a recent report from South India [ 28 ]. Traditional risk factors such as low BMI [ 29 , 30 ] and alcohol use [ 31 ] were associated with adverse outcomes; neither degree of hyperglygemia nor new DM was associated with unfavorable outcomes [ 28 ].…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to several retrospective reports and a systematic review in LMICs [ 8 , 11 , 27 ], our prospective analysis does not indicate an independent association between DM and composite unfavorable TB treatment outcome, consistent with a recent report from South India [ 28 ]. Traditional risk factors such as low BMI [ 29 , 30 ] and alcohol use [ 31 ] were associated with adverse outcomes; neither degree of hyperglygemia nor new DM was associated with unfavorable outcomes [ 28 ]. We found that low and normal BMI were more common among TB-DM participants than high BMI, a finding explained by studies that find that Indians generally have higher visceral adiposity index than their Western counterparts with the same body weight, leading to a high burden of insulin resistance, even among normal- or low-bodyweight Indians [ 28 , 32 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although, our data analyses were adjusted for these confounders, the differences in baseline demographics may still have influenced the treatment outcome in this patient cohort. It was recently observed that TB patients in India with a low BMI had a considerably longer time to sputum culture conversion and enhanced rates of treatment failure and death when compared to patients with a normal-to-high BMI (independent of DM status) [53]. Thus, demographic variables such as BMI or socioeconomic status might obscure the negative effects of DM on TB.…”
Section: Discussionmentioning
confidence: 99%
“…However, Nandakumar et al [ 44 ] found no correlation between diabetes control and TB treatment outcomes in their study conducted in Malappuram district of Kerala. In this context, it is interesting to note that recent studies have shown an association of poorly controlled diabetes with better outcomes in individuals with low body-mass index; this needs confirmation in larger studies [ 45 ].…”
Section: Effect Of Hyperglycemia and Glycemic Control On Infectionsmentioning
confidence: 99%